BioVaM in the Rat Model: A New Approach of Vascularized 3D Tissue for Esophageal Replacement - Hofmann, Alejandro D.; Hilfiker, Andres; Haverich, Axel; Andree, Birgit; Kuebler, Joachim; Ure, Benno (European Journal of Pediatric Surgery, 2015)
Introduction A major obstacle in tissue engineering is to create a surgically implantable tissue with long-term viability. Several promising techniques have focused on biological vascularized matrices (BioVaM) with preserved vascular pedicles in the porcine model. However, the handling of this model is time-consuming and expensive. Therefore, our aim was to establish a BioVaM in the rat.Materials and Methods Small bowel segments of Sprague-Dawley rats were isolated and perfused via cannulation of the superior mesenteric artery and the portal vein. All cellular matrix components were removed by sequential treatment with sodium dodecyl sulfate, sodium deoxycholate, and DNase. Quality of decellularization was investigated by histology and potential residual DNA by spectrophotometry. Primary endothelial cells (ECs) isolated from the major vessels of Sprague-Dawley rats. Cells were labeled with fluorescent cell tracker and injected into the vascular pedicles of the matrix. Attachment of ECs was assessed using fluorescence microscopy of the whole mount.Results Decellularized matrix demonstrated the absence of cellular components but conserved matrix architecture as determined by immune fluorescent, pentachrome, and hematoxylin and eosin stains. DNA content was reduced by more than 99%. ECs were characterized by specific staining against endothelial nitric oxide synthase and von Willebrand factor; when injected, ECs attached along the vessel walls including the capillaries of the intestinal wall.Conclusions Rat small bowel segments harvested with intact vascular pedicles and associated vascular network can be successfully decellularized and re-endothelialized ex vivo. This model is an inexpensive and easy to handle alternative and appears to be a promising approach for establishing vascularized tissue constructs.
Keywords: tissue engineering; rat model; vascular pedicles; vascularized tissue; re-endothelialization